(3GdMQGbGJs - (3GdYdGA Hf Sgds ((3Ydi Hf jMji Hf eMeO Hf CHj GdTcQ GdeZQHi s)
(3ChdgG (B:s
(3ef Mb Gdedc UeUGe GdOhdI hTeS GdedI Ydi ef YQa bOQ GdfYeI ai YfGjJg HEXgGQ GdYdhe MJi jTjY ai GdfGS PcQgG hbO ZHQJ OgQkG GHMK GdbOQI Ydi EMQGb LSe HVhA Ydi eSGaI HYjOI s
(3BNQgG (B:s
(3hef LejY HSjW OH V Edi fbWg C aJMQb YfOgG hPdc eG CQOfG Cf fHjf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(867) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs